Adaptive terminal sliding mode control scheme for synchronization of fractional-order uncertain chaotic systems. (October 2020) - Modiri, Arshia; Mobayen, Saleh
Abstract: The main goal in this article is synchronization of fractional-order uncertain chaotic systems in the finite time. For this aim, a terminal sliding mode controller with fractional sliding surface is employed to synchronize the states of two different fractional order chaotic systems with parameter uncertainties and external disturbances. This approach is robust when the effects of perturbations are derived into account. A fractional-order adaptive terminal sliding mode controller is developed to estimate the upper bounds of perturbations. Both suggested control laws are useful for fractional-order uncertain chaotic master–slave systems. Demonstrative simulation outcomes for Lorenz and Chen fractional-order systems with model perturbations and the engineering application on message telecommunication indicate the efficiency and usefulness of the recommended design. Highlights: Adaptive TSMC synchronizer for fractional-order master–slave chaotic systems. Finite-time convergence of synchronization errors to the origin. Online approximation of upper bounds of disturbances and uncertainties. Fractional-order calculation for stability analysis and controller design.